P12.03.B Ascorbate alters the hypoxic pathway in glioblastoma cellsin vitro and associates with improved patient survival. (5th September 2022) - Burgess, E R; Wiggins, G A R; Phillips, E; Morrin, H; Crake, R L I; Slatter, T; Royds, J; Vissers, M C M; Robinson, B A; Dachs, G U
Abstract: Background: Glioblastomas are highly aggressive and hypoxic tumours. This environment activates the hypoxic pathway, driving glioma progression and treatment resistance. The hypoxic pathway is regulated by the hypoxia inducible factor (HIF) hydroxylases, which require oxygen as a substrate. Under normoxic conditions, the HIF hydroxylases are active, causing degradation and inhibition of HIF transcription factors. Under hypoxia, the activity of the hydroxylases reduces and HIF accumulates, activating the hypoxic response. HIF hydroxylases also require ascorbate as a cofactor for optimal function. The brain has one of the highest ascorbate levels in the human body, yet data on ascorbate levels in gliomas is scarce. Cellular ascorbate uptake occurs through solute carrier family 23 member 2 (SLC23A2). My aim is to understand the relationship between ascorbate, SLC23A2 and the hypoxic pathway in brain cancer using both in vitro cell culture and clinical samples. Material and Methods: Ascorbate uptake was measured in human glioblastoma cell lines (T98G, U251MG, U87MG; ATCC) using reverse phase high performance liquid chromatography (HPLC-ECD). CRISPR-Cas was designed to knock-out SLC23A2 . Clinical glioblastoma samples (n=37) and follow-up data were provided by the Cancer Society Tissue Bank and University of Otago Dunedin. Ethics and informed consent were obtained (H19/163, MEC/08/02/016). Ascorbate levels, measured by HPLC-ECD, and HIF-1α and downstream targets were measured using Western blotting or ELISA. A HIF score was calculated from HIF-1α and downstream target protein levels to estimate hypoxic pathway activity. Results: In this study we have shown that T98G and U251 cells accumulate up to 15 nmol ascorbate/10 6 cells when exposed to 500 µM ascorbate for up to 24 hours, compared to U87MG cells with up to 3 nmol ascorbate/10 6 cells. Cancer Cell Line Encyclopaedia data shows that T98G and U251MG cells express higher levels of SLC23A2 compared to U87MG cells, aligning with our results. Clinical glioblastoma tissue contained a median of 7.6 µg ascorbate/100 mg tissue. Patients survival was significantly longer with above, vs below, median tumour ascorbate levels (Gehan-Breslow-Wilcoxon p = 0.027). The HIF score was negatively correlated with tumour ascorbate levels (Pearson r -0.327, p = 0.048). Patients with higher HIF-score had significantly shorter survival time compared to those with a lower HIF score (Gehan-Breslow-Wilcoxon p = 0.005). Conclusion: Ascorbate uptake in glioblastoma cells varies between cell lines and appears reliant on the level of SLC23A2 . Higher ascorbate content in clinical glioblastoma samples was associated with reduced hypoxic pathway activity and longer patient survival. Ongoing work, using SLC23A2 CRISPR-Cas knock-out cells, is investigating the effect of disrupting ascorbate uptake on hypoxic pathway signalling in glioblastoma cells.